A Landscape View of the Female Genital Tract Microbiome in Healthy Controls and Women With Reproductive Health Conditions Associated With Ectopic Pregnancy - Hui En Teh; Cheng Khee Pung; Valliammai Jayanthi Thirunavuk Arasoo; Polly Soo Xi Yap (Frontiers Media S.A., 2024)
Disruption of the female genital microbiome is associated with several pregnancy complications, including miscarriage, preterm onset of labour, and tubal pregnancy. Ectopic pregnancy is a known cause of maternal morbidity and mortality, but early diagnosis and treatment of ectopic pregnancy remain a challenge. Despite growing established associations between genital microbiome and female reproductive health, few studies have specifically focused on its link with ectopic pregnancy. Therefore, the current review aims to provide a comprehensive account of the female genital microbiome in healthy and fertile women compared to those in ectopic pregnancy and its associated risk factors. The microbial diversity from various sites of the female genital tract was explored for a reliable proxy of female reproductive health in sequencing-based ectopic pregnancy research. Our report confirmed the predominance of Lactobacillus in the vagina and the cervix among healthy women. The relative abundance decreased in the vaginal and cervical microbiome in the disease state. In contrast, there were inconsistent findings on the uterine microbiome across studies. Additionally, we explore a spectrum of opportunities to enhance our understanding of the female genital tract microbiome and reproductive conditions. In conclusion, this study identifies gaps within the field and emphasises the need for visionary solutions in metagenomic tools for the early detection of ectopic pregnancy and other gynaecological diseases.